Positive disposition in the prediction of strategic independence among millennials - Robert Konopaske; Eric G. Kirby; Susan L. Kirby (Administrative Sciences, 2017)
Research on the dispositional traits of Millennials (born in 1980-2000) finds that this generation, compared to earlier generations, tends to be more narcissistic, hold themselves in higher regard and feel more entitled to rewards. The purpose of this intragenerational study is to counter balance extant research by exploring how the positive dispositional traits of proactive personality, core self-evaluation, grit and self-control predict strategic independence in a sample of 311 young adults. Strategic independence is a composite variable measuring a person's tendency to make plans and achieve long-term goals. A confirmatory factor analysis and hierarchical regression found evidence of discriminant validity across the scales and that three of the four independent variables were statistically significant and positive predictors of strategic independence in the study. The paper discusses research and practical implications, strengths and limitations and areas for future research.
Keywords: 350; strategic independence; proactive personality; grit; core self-evaluation; self-control; careers; transition; Millennials